(untitled) (The Pretoria Student Law Review, 2021)
In the following article I will critically analyse the concept of hate speech as it was considered in the South African Human Rights Commission’s (the ‘Commission’) report on utterances made by Julius Malema (the ‘report’).2 The critique will be delivered by way of Critical Race Theory (CRT) as I aim to illustrate the Commission’s narrow interpretation of racism in light of hate speech. Because the Commission relies on an array of court judgments and equality legislation to form its equality jurisprudence on hate speech, my critique will also set out to show that the Commission’s equality jurisprudence is reflective of the Constitution and the courts’ narrow understanding of racism. I aim to argue that a narrow understanding of racism leads to a very abstract equality jurisprudence.